2007
DOI: 10.1002/anie.200703409
|View full text |Cite
|
Sign up to set email alerts
|

Poly(anthrylenebutadiynylene)s: Precursor‐Based Synthesis and Band‐Gap Tuning

Abstract: The utility of conjugated polymers in such diverse applications as sensors, photovoltaic devices, light-emitting diodes, field-effect transistors, and electrochromic devices stems in large part from the ability of chemists to systematically modify the properties of these materials through structural variation. A powerful strategy for varying the electronic structure of organic polymers involves modulating the degree of quinoid character of the conjugated backbone. Decreasing the energy difference between aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 32 publications
(15 reference statements)
2
26
0
Order By: Relevance
“…Out-of-plane twisting of the phenyl ring from the central anthracene possibly deteriorates the extended π-conjugation through compound 1, [18] whereas the longest effective conjugation length of 2 may be due to the coplanar conformation of the anthracene and ethynylene groups, as reported before. [19] It can be seen from Table 1 that the optical HOMO-LUMO gap of 3 is smaller than that of 1, indicating a greater delocalization of electrons in 3. This result confirms that changing the electron affinity of the acceptors could effectively modulate the HOMO-LUMO gaps of the molecules and that the benzowww.eurjoc.orgthiadiazole moiety is a stronger electron acceptor than the anthracene moiety; however, this argument fails to explain the similarity of the HOMO-LUMO gaps between 2 and 4, which have anthracene and benzothiadiazole moieties as their acceptors.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Out-of-plane twisting of the phenyl ring from the central anthracene possibly deteriorates the extended π-conjugation through compound 1, [18] whereas the longest effective conjugation length of 2 may be due to the coplanar conformation of the anthracene and ethynylene groups, as reported before. [19] It can be seen from Table 1 that the optical HOMO-LUMO gap of 3 is smaller than that of 1, indicating a greater delocalization of electrons in 3. This result confirms that changing the electron affinity of the acceptors could effectively modulate the HOMO-LUMO gaps of the molecules and that the benzowww.eurjoc.orgthiadiazole moiety is a stronger electron acceptor than the anthracene moiety; however, this argument fails to explain the similarity of the HOMO-LUMO gaps between 2 and 4, which have anthracene and benzothiadiazole moieties as their acceptors.…”
Section: Resultsmentioning
confidence: 96%
“…This phenomenon may be attributed to the greater interaction between the anthracene and ethynylene groups than that between the benzothiadiazole and ethynylene groups. [19] In addition to the acceptors combined to the donor chromophores, π-bridges are also known to play an important role in determining the conjugation lengths of these compounds. [20] In this case, insertion of an ethynylene spacer results in longer onset wavelengths of 2 and 4 than those of 1 and 3, indicating longer effective conjugation lengths and smaller HOMO-LUMO gaps of 2 and 4 than those of 1 and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In 2007, Taylor and Swager demonstrated that the Sn II /HCl‐mediated reduction could be used for the synthesis of anthracene‐based polymer 46 a (Scheme ) . Tykwinski and co‐workers utilized a related approach to synthesize a series of conjugated pentacene oligomers, such as trimer 46 b , as well as a series of oligopentacene‐based chromophores assembled via click chemistry .…”
Section: Snii‐mediated Reduction Of Diolsmentioning
confidence: 99%
“…For example, conjugated oligomers and polymers of anthracene have promising charge-carrier mobilities and continue to be explored [3,4,5,6,7,8,9,10,11], even though anthracene is not regarded as a particularly good organic semiconductor for thin film applications. On the other hand, pentacene, a benzannulated relative of anthracene in the linear oligoacene family, has technologically relevant charge-carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%